Spectropolarimetry of the superwind filaments of the starburst galaxy M 82 II: Kinematics of the dust surrounding the nuclear starburst. (14th August 2019) - Yoshida, Michitoshi; Kawabata, Koji S; Ohyama, Youichi; Itoh, Ryosuke; Hattori, Takashi
Abstract: We performed deep spectropolarimetric observations of the prototypical starburst galaxy M 82 with the Subaru Telescope in order to study the kinematics of the dust outflow. We obtained optical polarized emission-line spectra up to ∼4 kpc away from the nucleus of the galaxy along three position angles, 138°, 150°, and 179° within the conical outflowing wind (superwind). The Hα emission line in the superwind is strongly polarized and the polarization pattern shows dust scattering of central light sources, being consistent with the previous works. The intensity weighted polarization degree of the Hα line reaches ∼30% at maximum. There are at least two light sources at the central region of the galaxy; one is located at the near-infrared nucleus and the other resides at one of the peaks of the 3 mm radio and molecular gas emission. The outer (>1 kpc) dust is illuminated by the former, whereas the inner dust is scattering the light from the latter. We also investigated the dust motion from the velocity field of the polarized Hα emission line. The dust is accelerated outward on the northwest side of the nucleus. A simple bi-conical dust outflow model shows that the outflow velocity of the dust reaches ≳ 300–450 km s −1 at ∼4 kpc from the nucleus, suggesting that some portion of the dust escapes from the gravitational potential of M 82 into the intergalactic space. At some regions on the southeast side, in particular along the position angle of 138°, the dust has a radial velocity that is slower than the systemic velocity of the galaxy, apparently suggesting inflowing motion toward the nucleus. These components are spatially consistent with a part of the molecular gas stream, which is kinematically independent of the outflow gas; thus the apparent inflow motion of the dust reflects the streaming motion associated with the molecular gas stream.